Slightly and Moderately Lame Cows in Tie Stalls Behave Differently From Non-lame Controls. A Matched Case-Control Study - Bernhard, Johanna Karin; Vidondo, Beatriz; Achermann, Rahel Lisa; Rediger, Rahel; Stucki, Dimitri; Müller, Kerstin Elisabeth; Steiner, Adrian (Frontiers in Veterinary Science, 2020)
Lameness affects dairy cows worldwide and is usually associated with pain. Behavioral differences in lame compared to non-lame tie-stall-housed dairy cows might be less pronounced than in free-stall-housed, since the principle demands to a cow’s locomotor system and thus the impact of lameness on behavior seem to be lower in tie stalls. Behavioral differences between lame and non-lame cows might be used to estimate the impact of lameness on the well-being of tied dairy cows. In the current study, lame cows were categorized as locomotion scoring between 2.25 and 3.25 on a 1 – 5 scale. The aim was to compare the eating, rumination and lying behavior of lame cows against non-lame tied dairy cows, in order to draw conclusions on the association of lameness, behavior and well-being in tied dairy cows. The eating and rumination behavior of 26, the lying behavior of 30, and the relative upright and lying activities of 25 matched case-control pairs were analyzed, considering the matching criteria farm, breed-type, and parity-group. Lame cows had fewer (mean of the pairwise differences (case – control) (meandiff) = -2.6 bouts, CI95% [-3.8 – -1.4] bouts, p = 0.001), but longer lying bouts (meandiff = 26.7 min per bout, CI95% [10.1 – 43.4] min per bout, p = 0.006). The lying time was shorter (meandiff = -64.7 min, CI95% [-104.4 – -24.9] min, p = 0.006) in lame cows compared to their non-lame controls. Lame cows had a shorter eating time (meandiff = -27.7 min, CI95% [-51.5 – -4.0] min, p = 0.042) and spent a larger proportion of their upright time ruminating (meandiff = 7.2 %, CI95% [3.2 – 11.1] %, p = 0.001) instead of eating. The results of the current study indicate that the eating, rumination, and lying behavior of lame tied dairy cows is altered. These findings indicate that slight and moderate lameness (locomotion score between 2.25 and 3.25 on a 1 – 5 scale) are likely to be associated with an impaired well-being in affected tied dairy cows. This underlines the need to continuously reduce the lameness prevalence and severity in tied dairy herds.